2023
DOI: 10.1186/s12894-023-01347-x
|View full text |Cite
|
Sign up to set email alerts
|

Application of tip-bendable ureteral access sheath in flexible ureteroscopic lithotripsy: an initial experience of 224 cases

Hui Liang,
Lijian Liang,
Yiwei Lin
et al.

Abstract: Introduction During the last decades, the advent of flexible ureteroscopic lithotripsy has revolutionized the management of upper urinary tract stones. We designed a patented tip-bendable ureteral access sheath to facilitate stone clearance. Our current study reported our initial experience of 224 cases. Materials and methods The study is a descriptive, retrospective analysis. The initial 224 cases, operated consecutively by one surgeon during 16 m… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…Various complications in the use of FANS have been reported. Chen et al [46] reported only two cases of fever in a cohort of 53 patients who underwent FURS with FANS, while Liang et al [58] recorded an even lower fever rate (2/224). In another study, 10/12 Fr FANS have been compared to 12/14 Fr, reporting four cases of fever for the first group and no infectious complications for the second group [47].…”
Section: Complicationsmentioning
confidence: 98%
“…Various complications in the use of FANS have been reported. Chen et al [46] reported only two cases of fever in a cohort of 53 patients who underwent FURS with FANS, while Liang et al [58] recorded an even lower fever rate (2/224). In another study, 10/12 Fr FANS have been compared to 12/14 Fr, reporting four cases of fever for the first group and no infectious complications for the second group [47].…”
Section: Complicationsmentioning
confidence: 98%
“…The stone clearance rate was 93.8 % ( 31/33 ), the operation time was short, the intraoperative blood loss was small, and the hospitalization time was short, indicating that FURL was an efficient surgical method. Hui Liang [10]also believed that FURL had minimal trauma and rapid postoperative recovery. However, the incidence of FURL complications in this study was 18.2 % higher than that of Yong Sun Choi [11] ; there was a significant difference in the incidence of complications between 6.9 % and 13.3 % in O Baş et al [12].…”
Section: Discussmentioning
confidence: 99%
“…The introduction of the new TFS-UAS, featuring a bendable distal end that reaches directly to the calyx and facilitates the removal of irritant and stone fragments with low negative pressure, has led to a better clearance effect compared to T-UAS. This expansion has broadened the indications for endoscopic surgery [12].…”
Section: Introductionmentioning
confidence: 99%
“…Currently, the combination of the TFS-UAS with a DFU is primarily used to treat kidney stones smaller than 2 cm and has demonstrated good clinical e cacy [12][13][14]. There has been relatively limited research on applying this technology to treat stones with a diameter of 2-4 cm.…”
Section: Introductionmentioning
confidence: 99%